Effect of Fe3O4 nanoparticles on the performance of anaerobic digestion through electrochemical analysis. Issue 26 (23rd November 2022) - Gong, Lei; Zuo, Tong; Qian, Yi; Liu, Jianbo; Zhou, Jun; Zhang, Haonan; Wang, Jin; Zhou, Ying; Yang, Xiaoqi; Wang, Luyu; Jia, Qinwei
ABSTRACT: In view of the high cost and complex operation of the traditional chemical method for the determination of the anaerobic digestion (AD) process, this study investigated the feasibility of using electrochemistry analysis to determine the effect of Fe3 O4 nanoparticles (NPs) on the AD process. The quantity of electric charge of Fe3 O4 NPs modified graphite electrode in sodium acetate electrolyte was higher than that of graphite electrode. The addition of Fe3 O4 NPs was beneficial to improve the electrochemical activity of the electrode. On this basis, enzymes and microorganisms were extracted from anaerobic reactors containing different concentrations of Fe3 O4 NPs to make electrodes respectively to further investigate the effects of Fe3 O4 NPs on enzyme and microbial activities in AD. The electrochemical analysis results of the enzyme electrodes and microbial electrodes showed that the quantity of electric charge produced by the group of 200 mg/L Fe3 O4 NPs was the highest. The cumulative biogas production of 200 mg/L Fe3 O4 NPs was 809 mL/g VS, and better than other groups. These results showed that 200 mg/L Fe3 O4 NPs was the best dosage, and the electrochemical analysis has higher sensitivity in the AD detection. Highlight Electrochemistry was used to investigate the activities of enzymes and microorganisms in anaerobic digestion. The effects of Fe3 O4 nanoparticles on different stages of anaerobic digestion were analyzed by electrochemical method. The feasibility of electrochemical analysis was verified from the perspective of microbiology. GRAPHICAL ABSTRACT: UF0001